International travel in the immunocompromised patient: a cross‐sectional survey of travel advice in 254 consecutive patients. Issue 6 (June 2015) - Bialy, C.; Horne, K.; Dendle, C.; Kanellis, J.; Littlejohn, G.; Ratnam, I.; Woolley, I.
Abstract Aims Our primary aim was to determine the rate of overseas travel in immunocompromised individuals attending appropriate clinics at an Australian tertiary care hospital. We also aimed to characterise health‐seeking behaviour prior to travel and investigated sources of pre‐travel advice, compared travel patterns and activities between three specific immunosuppressed groups, and examined pre‐immunosuppression patient serology. Methods We implemented a cross‐sectional survey of patients between February and August 2012. This survey was implemented among three outpatient populations at Monash Medical Centre, an Australian tertiary care hospital. Results We recruited 254 immunosuppressed adults from three patient populations: human immunodeficiency virus‐positive individuals, renal transplant patients and rheumatology patients requiring immunosuppressive therapy. No clinical intervention was performed. In the 10 years preceding the survey, 153 (60.2%) participants reported international travel. Of these, 105 (68.6%) were immunosuppressed at the time of travel. These patients were 47.6% male and 60% Australian born. Forty per cent were visiting friends and relatives as part of their travel. Fifty‐four per cent of those immunocompromised at the time of travel were going to high‐risk destinations. Pathology files indicated that serological screening was frequently not performed prior to immunosuppression in the renal transplant and rheumatology groups. Conclusions Immunocompromised patients often travel to high‐risk destinations with limited or inadequate pre‐travel preparations. Doctors caring for the immunocompromised should be aware of travel risks, suitable vaccination protocols and when to refer to specialist travel clinics.